Preparation of a copper-based catalyst and its application in synthesis of 1,4-butanediol by hydrogenation of dimethyl succinate

CN122912872APending Publication Date: 2026-10-16SHANDONG YUANLI TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611416355.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但这类催化剂普遍存在选择性不足的问题:丁二酸二甲酯催化加氢过程中除了生成目标产物BDO还会发生分子内成环,生成THF,这不仅降低了BDO的收率与产品纯度,还增加了后续分离提纯的能耗

Benefits of technology

[0015] 1. This invention involves adding tris(hydroxymethyl)aminomethane (Tris) to the impregnation solution to form a composite additive system with citric acid and polyethylene glycol. Citric acid preferentially reacts with Al... 3+ It forms negatively charged chelated anion clusters, while Mn 2+ and some Al 3+ They still coexist in the form of free hydrated cations. Negatively charged chelate clusters preferentially accumulate on the CuO matrix surface through electrostatic attraction, forming local negative charge anchors; protonated Tris cations form ion pairs with surface anchors through electrostatic attraction and are carried to the CuO surface layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912872A_ABST
    Figure CN122912872A_ABST
Patent Text Reader

Abstract

The application discloses a kind of preparation of copper-based catalyst and its application in dimethyl succinate hydrogenation synthesis 1,4-butanediol, belong to catalytic preparation technical field.The application discloses a kind of preparation method of copper-based catalyst, it is characterized in that, including steps: pre-calcination, preparation metal salt composite solution, impregnation granulation and calcination;Trimethylol aminomethylane is dissolved in solvent, citric acid is added and stirred until completely dissolved;Subsequently, metal additive precursor is added, and stirring is continued until the solid is completely dissolved;Then, the pH of the system is adjusted to 4.5-5.0, and finally, polyethylene glycol is added, and the metal salt composite solution is obtained after mixing uniformly.The copper-based catalyst prepared by the application has high activity, high selectivity and excellent thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst preparation technology, and specifically relates to the preparation of a copper-based catalyst and its application in the hydrogenation synthesis of 1,4-butanediol from dimethyl succinate. Background Technology

[0002] 1,4-Butanediol (BDO) is an important organic chemical raw material widely used in the production of tetrahydrofuran (THF), gamma-butyrolactone (GBL), polyurethane (PU), polybutylene terephthalate (PBT), and biodegradable plastics (such as PBAT and PBS). In recent years, with the rapid development of new energy vehicles, biodegradable plastics, and spandex industries, the market demand for BDO has continued to rise. China has become the world's largest producer and consumer of BDO, with both production capacity and average annual growth rate reaching high levels. Among the preparation processes of 1,4-butanediol, the maleic anhydride hydrogenation method is considered the most technically and economically efficient BDO production route due to its advantages such as lower energy consumption, relatively less equipment investment, and a relatively simple process route. This process uses n-butane as a raw material, which is oxidized to obtain maleic anhydride. Maleic anhydride is then esterified with methanol to produce dimethyl maleate. Dimethyl maleate is hydrogenated to produce dimethyl succinate, which is further hydrogenated and hydrolyzed to obtain BDO. The hydrogenation of dimethyl succinate to BDO is the core step in this process, and the performance of the catalyst in this step directly determines the conversion rate of DMS, the selectivity of BDO, and the overall production efficiency and energy consumption of the unit.

[0003] In the hydrogenation reaction of dimethyl succinate to BDO, copper-based catalysts are the most widely used due to their excellent selectivity for ester carbonyl hydrogenation and relatively low cost. Early industrial applications primarily used copper-chromium catalysts, such as the copper-chromium catalyst disclosed in Chinese patent application CN105709760A, which can achieve high hydrogenation activity by controlling the dispersibility and stability of copper species through the chromium component. However, chromium is a highly toxic heavy metal, and the catalyst preparation and disposal processes can easily cause serious environmental pollution, which does not meet the requirements of current green chemical engineering and environmental protection policies. Chromium-free catalysts have become an inevitable development direction for copper-based ester hydrogenation catalysts.

[0004] To replace chromium-containing catalysts, various chromium-free copper-based catalytic systems have been developed in this field, among which co-precipitation catalysts, represented by copper-manganese-aluminum (CMA) and copper-zinc-aluminum (CZA), are the most widely studied. For example, Chinese patent CN102784651B discloses a copper-zinc-cerium co-precipitation hydrogenation catalyst, and Chinese patent application CN201210256740A discloses a CMA catalyst prepared by ammonia precipitation, both of which have shown certain catalytic performance in the hydrogenation reaction of dimethyl succinate. However, these catalysts generally suffer from insufficient selectivity: in the catalytic hydrogenation of dimethyl succinate, in addition to generating the target product BDO, intramolecular cyclization occurs, generating THF. This not only reduces the yield and purity of BDO but also increases the energy consumption for subsequent separation and purification. Related studies have shown that the distribution of aluminum species is difficult to control precisely during the co-precipitation process, making it difficult to effectively suppress the side reaction of BDO dehydration to THF.

[0005] Besides selectivity defects, insufficient thermal stability of copper-based catalysts is also a core bottleneck restricting their long-term operation. Copper's Taman temperature is only 300℃. Under high-temperature hydrogenation reaction conditions, active copper species easily aggregate and grow through grain boundary migration, leading to a significant reduction in the number of active sites and irreversible degradation of catalyst activity. Yang Hao et al., in their research report "Research Progress on New Technologies for the Preparation of Copper-Based Catalysts Based on Co-precipitation Method" published in *Chemical Industry and Engineering Progress*, 2014, pointed out that conventional co-precipitated copper-based catalysts, when operating at temperatures above 200℃ for extended periods, exhibit copper grain growth rates exceeding 30%, making it difficult to meet the long-term operation requirements of large-scale industrial plants. To improve anti-sintering performance, existing technologies often employ methods such as adding rare earth additives or loading onto high specific surface area supports. For example, Chinese patent CN103769157B improves catalyst stability through a two-step co-precipitation combined with supercritical drying technology. However, these approaches either involve cumbersome process steps and demanding equipment requirements, or the inert support dilutes the concentration of active components, leading to a decrease in catalyst volumetric activity, making it difficult to balance activity and stability.

[0006] Furthermore, in pursuit of higher catalytic performance, some research has turned to the development of catalysts with special structures, such as hollow core-shell structures and confined copper-based catalysts. Although these catalysts can balance activity and stability to a certain extent, their preparation process generally involves complex template agents, special atmosphere calcination, supercritical drying, or expensive precursors, which significantly increases the production cost of the catalysts and the difficulty of industrial scale-up, making it difficult to achieve large-scale industrial applications.

[0007] To address the aforementioned common problems, numerous targeted improvement studies have been conducted in this field. Among them, Chinese patent CN103566945B discloses a copper-manganese-aluminum catalyst for the hydrogenation of dimethyl succinate to 1,4-butanediol. This catalyst is prepared by simultaneously precipitating copper, manganese, and aluminum components using a co-precipitation method, which improves the hydrogenation activity of the chromium-free catalyst to some extent. However, in this co-precipitation process, it is difficult to achieve uniform dispersion of aluminum and copper species, and the side reaction of BDO dehydration to THF remains significant.

[0008] Chinese patent application CN117258798A discloses a supported copper-based ester hydrogenation catalyst, which improves the dispersibility and anti-sintering properties of copper species by impregnating copper and an additive onto a porous oxide support, utilizing the physical confinement effect of the support. However, this approach also has technical limitations: firstly, the inert support provides channels and support, typically accounting for more than 30%, resulting in a low proportion of active catalytic metal and low industrial utilization; secondly, the chemical bond between copper and the support is weak, and copper species can still easily migrate and sinter along the support channels under high-temperature hydrogen-rich conditions, resulting in a generally poor anti-sintering effect.

[0009] In summary, existing copper-based catalysts for the hydrogenation of dimethyl succinate (BDO) still struggle to simultaneously meet the multiple requirements of high activity, high selectivity, long lifespan, environmental friendliness, and low preparation cost: chromium-free coprecipitation catalysts suffer from inherent defects such as poor selectivity and easy sintering; supported modified catalysts sacrifice volumetric activity for stability and have insufficient side reaction suppression; and similar improvement schemes cannot simultaneously solve the dual problems of numerous side reactions and copper species sintering under a simplified process. Therefore, developing a novel chromium-free copper-based catalyst with a simple process, requiring no complex equipment or expensive raw materials, and effectively suppressing side reactions such as THF while improving the anti-sintering properties of copper species, has significant industrial application value for promoting the green upgrading of BDO production processes. Summary of the Invention

[0010] To address the shortcomings of existing technologies, this invention provides a method for preparing a copper-based catalyst and its application in the hydrogenation synthesis of 1,4-butanediol from dimethyl succinate. The prepared copper-based catalyst exhibits high activity, high selectivity, and excellent thermal stability.

[0011] To achieve the above-mentioned technical objectives, the technical solution adopted by the present invention is as follows: A method for preparing a copper-based catalyst includes the following steps: pre-calcination, preparation of a metal salt composite solution, impregnation granulation, and calcination; (1) Pre-baking The copper precursor is mixed with diammonium ethylenediaminetetraacetate and ground for 15-20 min to obtain a copper precursor mixture. The copper precursor mixture is heated to 180-220℃ at a rate of 1.5-2.5℃ / min and held at that temperature for 0.8-1.2 h. The temperature is then further increased to the calcination temperature of 350-550℃ and held at that temperature for 2-4 h to obtain a copper oxide matrix. The copper precursor is one of copper nitrate, copper sulfate, and copper acetate. The mass ratio of the copper precursor to diammonium ethylenediaminetetraacetate is 100:3-4; During the pre-calcination step, maintaining a constant temperature of 180-220℃ for 0.8-1.2 hours allows the additives to gradually complex and decompose; maintaining a constant temperature of 350-550℃ for 2-4 hours ensures complete removal of the additives and the formation of a stable porous copper oxide matrix.

[0012] (2) Preparation of metal salt composite solution Tris(hydroxymethyl)aminomethane (Tris) was dissolved in a solvent, and citric acid was added and stirred until completely dissolved. Then, a metal precursor was added and stirred until the solid was completely dissolved. The pH of the system was then adjusted to 4.5-5.0, and finally polyethylene glycol was added. After mixing evenly, a metal salt composite solution was obtained. The metal additive precursor is a mixture of manganese nitrate and aluminum nitrate in a mass ratio of 10:24-26. The solvent is a mixture of water and ethanol in a mass ratio of 10:8-12; The mass ratio of the metal additive precursor, tris(hydroxymethyl)aminomethane, citric acid, polyethylene glycol, and solvent is 10-15:3.5-4.5:4-5:2-3:100.

[0013] (3) Impregnation granulation The metal salt composite solution was dropped onto the copper oxide matrix and continuously shaken until the content of fine powder smaller than 2 mm in the system was less than 5% of the total mass, and the wet particles with a particle size of 3-6 mm accounted for more than 80% of the total mass. The shaking was then stopped. The mixture was then sealed and allowed to stand at room temperature for 2-3 hours, then allowed to stand under ventilation for 2-3 hours, and then dried at 50-80℃ for 10-14 hours to obtain copper-based catalyst precursor particles. The mass ratio of the metal salt composite solution to the copper oxide matrix is ​​10:0.65-0.75.

[0014] (4) Roasting The copper-based catalyst precursor particles were calcined in air under controlled temperature in stages to obtain the copper-based catalyst. The staged temperature-controlled calcination is as follows: first, the temperature is increased to 230-250℃ at 1-3℃ / min and held at this temperature for 1-2 hours; then, the temperature is increased to 450-550℃ at 2-5℃ / min and held at this temperature for 3-5 hours to obtain the copper-based catalyst. Beneficial effects

[0015] 1. This invention involves adding tris(hydroxymethyl)aminomethane (Tris) to the impregnation solution to form a composite additive system with citric acid and polyethylene glycol. Citric acid preferentially reacts with Al... 3+ It forms negatively charged chelated anion clusters, while Mn 2+ and some Al 3+ They still coexist in the form of free hydrated cations. Negatively charged chelate clusters preferentially accumulate on the CuO matrix surface through electrostatic attraction, forming local negative charge anchors; protonated Tris cations form ion pairs with surface anchors through electrostatic attraction and are carried to the CuO surface layer.

[0016] 2. This invention employs a composite additive system containing citric acid, Tris, etc., which is impregnated and adsorbed onto the pores and surface of the copper substrate. Citric acid begins to decompose at approximately 175°C, and its coordination protection effect weakens accordingly. Tris decomposes at an even higher temperature; when the temperature rises to 230-250°C, Tris decomposes to produce nitrogen-containing organic fragments and carbon-containing residues. These substances remain on the CuO surface and affect the adjacent Al... 3+ Mn 2+ It creates spatial isolation, inhibiting its migration and aggregation; in Al 3+ Mn 2+ While maintaining a dispersed state, the temperature is kept constant for 1-2 hours, allowing Al, Mn, and other metal species to undergo preliminary nucleation and fixation in situ, achieving uniform pre-dispersion. This pre-dispersion state lays the structural foundation for subsequent high-temperature crystallization, effectively suppressing long-range migration and aggregation of metal atoms at high temperatures. The uniformly distributed Al and Mn species can fully contact and tightly bond with the CuO matrix, effectively promoting solid-state reactions and facilitating the full and uniform formation of the copper-aluminum spinel active phase, ensuring the high dispersion and structural stability of the final catalyst active components.

[0017] 3. Utilizing the synergistic effects of EDTA diammonium pre-calcination for pore formation and the combined effects of composite additives for controlled dispersion, the catalyst of this invention forms a mesoporous channel structure with concentrated pore size and excellent interconnectivity, significantly improving specific surface area and pore volume. This well-organized pore structure provides ample active sites for the hydrogenation reaction, accelerates reactant diffusion and rapid product desorption, and prevents products from remaining in the pores for extended periods, thus avoiding deep side reactions and further ensuring the high efficiency and stability of the catalytic reaction.

[0018] 4. Performance verification through fixed-bed hydrogenation experiments demonstrates that the chromium-free copper-based catalyst prepared in this invention exhibits excellent and stable catalytic performance. The conversion rate of dimethyl succinate reaches over 99.98%, the selectivity for 1,4-butanediol is not less than 96.13%, and the selectivity for tetrahydrofuran byproducts is as low as 2.11% or less, exhibiting significant side reaction suppression. Long-term stability testing results show that after 1000 hours of continuous stable operation, the catalyst's activity and selectivity show no significant decline; after aging at 500℃ for 10 hours, the catalyst activity decreases by less than 2%, demonstrating excellent anti-sintering ability and thermal stability. Attached Figure Description

[0019] Figure 1 The image shows the XRD pattern of the copper-based catalyst prepared in Example 1. Figure 2 The image shows the BET adsorption isotherm of the copper-based catalyst prepared in Example 1. Figure 3 The image shows the BET adsorption pore size distribution of the copper-based catalyst prepared in Example 1. Detailed Implementation

[0020] To facilitate understanding of the present invention, the following embodiments are provided. These embodiments are merely illustrative and should not be considered as specific limitations of the invention. Because the present invention can also be described and explained through other solutions that do not depart from its technical features, all modifications within the scope of the present invention or its equivalents should fall within the protection scope of the present invention.

[0021] The present invention will be further illustrated below with reference to embodiments, comparative examples, and application examples.

[0022] Example 1 This embodiment provides a method for preparing a copper-based catalyst, including the following steps: (1) Pre-baking Copper sulfate pentahydrate and diammonium ethylenediaminetetraacetate were mixed at a mass ratio of 156:3.5 and ground for 18 min to obtain a copper precursor mixture. The copper precursor mixture was placed in a muffle furnace and heated to 200℃ at a rate of 2℃ / min, and held at that temperature for 1.0 h; then the temperature was further increased at a rate of 2℃ / min to a calcination temperature of 450℃, and held at that temperature for 3 h to obtain a copper oxide matrix.

[0023] (2) Preparation of metal salt composite solution Weigh the following components according to the following mass ratio: 12 parts of metal auxiliary precursor (manganese nitrate and aluminum nitrate mixed at a mass ratio of 10:25), 4.0 parts of tris(hydroxymethyl)aminomethane, 4.5 parts of citric acid, 2.5 parts of polyethylene glycol (PEG-400), and 100 parts of solvent (water and ethanol mixed at a mass ratio of 10:10).

[0024] Tris(hydroxymethyl)aminomethane (Tris) was dissolved in a solvent, and citric acid was added and stirred until completely dissolved. Then, a metal precursor was added and stirred until the solid was completely dissolved. The pH of the system was then adjusted to 4.7, and finally polyethylene glycol was added. After mixing evenly, a metal salt composite solution was obtained.

[0025] (3) Impregnation granulation The metal salt composite solution obtained in step (2) was added dropwise to the copper oxide matrix obtained in step (1), controlling the mass ratio of the metal salt composite solution to the copper oxide matrix to be 10:0.7, while shaking. Shaking continued until the content of fine powder smaller than 2 mm in the system was less than 5% of the total mass, and the wet particles with a particle size of 3-6 mm accounted for more than 80% of the total mass, at which point shaking was stopped. Then, the mixture was sealed and allowed to stand at room temperature for 2.5 h, allowed to stand under ventilation for 2.5 h, and then dried at 65 °C for 12 h to obtain copper-based catalyst precursor particles.

[0026] (4) Staged temperature-controlled roasting The copper-based catalyst precursor particles obtained in step (3) were placed in a muffle furnace and calcined in stages under air atmosphere: first, the temperature was increased to 240℃ at 2℃ / min and kept constant for 1.5 h; then the temperature was increased to 500℃ at 3.5℃ / min and kept constant for 4 h to obtain the copper-based catalyst.

[0027] The copper-based catalyst obtained in Example 1 was determined by XRF analysis, and the mass percentages of Cu, Al, and Mn were: Cu 76.63%, Al 10.86%, and Mn 11.38%.

[0028] Appendix Figure 1 The image shows the XRD pattern of the copper-based catalyst prepared in Example 1. Figure 1 As shown, the most significant diffraction peak of CuO is at 2θ=35.5°, indicating that copper mainly exists in the form of CuO with a monoclinic crystal system and good crystallinity. Diffraction peaks of CuAl2O4 (copper aluminum spinel) appear at 31.3°, 36.9°, and 44.9°. The diffraction peak at 44.9° is close to the characteristic peak of the (111) crystal plane of CuO (44.5°), and the two overlap. A diffraction peak of copper manganese spinel phase appears at 37.2°, indicating that Mn has partially embedded in the CuO lattice, forming a Cu-Mn composite oxide solid solution. The formation of these spinel phases can enhance the interaction between the active component and the matrix, which is beneficial to improving the thermal structural stability of the catalyst.

[0029] Appendix Figure 2 The attached diagram shows the BET adsorption isotherm of the copper-based catalyst prepared in Example 1. Figure 3The image shows the BET adsorption pore size distribution of the copper-based catalyst prepared in Example 1. The BET adsorption detection conditions were: N2 physical adsorption-desorption method, measured at 77 K (liquid nitrogen temperature). The samples were degassed at 200 °C for 2 hours before testing.

[0030] The copper-based catalyst prepared in Example 1 has a specific surface area of ​​36.8 m². 2 / g, pore volume 0.28cm 3 / g.

[0031] From the appendix Figure 3 It can be seen that the pore size distribution of the catalyst is parabolic, concentrated in the mesoporous range of 10-30 nm, and reaches a peak at about 15 nm. This indicates that the catalyst has a regular and concentrated mesoporous channel structure, which is conducive to the diffusion of reactant molecules and the rapid desorption of product molecules.

[0032] Example 2 This embodiment provides a method for preparing a copper-based catalyst, including the following steps: (1) Pre-baking Copper nitrate trihydrate and diammonium ethylenediaminetetraacetate were mixed at a mass ratio of 129:3 and ground for 15 min to obtain a copper precursor mixture. The copper precursor mixture was placed in a muffle furnace and heated to 180℃ at a rate of 1.5℃ / min, and held at that temperature for 1.2 h. Then, the temperature was further increased at a rate of 1.5℃ / min to a calcination temperature of 350℃, and held at that temperature for 4 h to obtain a copper oxide matrix.

[0033] (2) Preparation of metal salt composite solution Weigh the following components according to the following mass ratio: 10 parts of metal auxiliary precursor (manganese nitrate and aluminum nitrate mixed in a mass ratio of 10:24), 3.5 parts of tris(hydroxymethyl)aminomethane, 4 parts of citric acid, 2 parts of polyethylene glycol (PEG-400), and 100 parts of solvent (water and ethanol mixed in a mass ratio of 10:8).

[0034] Tris(hydroxymethyl)aminomethane (Tris) was dissolved in a solvent, and citric acid was added and stirred until completely dissolved. Then, a metal precursor was added and stirred until the solid was completely dissolved. The pH of the system was then adjusted to 4.5, and finally polyethylene glycol was added. After mixing evenly, a metal salt composite solution was obtained.

[0035] (3) Impregnation granulation The metal salt composite solution obtained in step (2) was added dropwise to the copper oxide matrix obtained in step (1), controlling the mass ratio of the metal salt composite solution to the copper oxide matrix to be 10:0.65, while shaking. Shaking continued until the content of fine powder smaller than 2 mm in the system was less than 5% of the total mass, and the wet particles with a particle size of 3-6 mm accounted for more than 80% of the total mass, at which point shaking was stopped. Then, the mixture was sealed and allowed to stand at room temperature for 2 hours, then allowed to stand under ventilation for 2 hours, and finally dried at 50°C for 14 hours to obtain copper-based catalyst precursor particles.

[0036] (4) Staged temperature-controlled roasting The copper-based catalyst precursor particles obtained in step (3) were placed in a muffle furnace and calcined in stages under air atmosphere: first, the temperature was increased to 230℃ at 1℃ / min and kept constant for 2 h; then the temperature was increased to 450℃ at 2℃ / min and kept constant for 5 h to obtain the copper-based catalyst.

[0037] The copper-based catalyst obtained in Example 2 was determined by XRF analysis. The mass percentages of Cu, Al, and Mn were: Cu 74.37%, Al 11.10%, and Mn 10.31%. The specific surface area of ​​the catalyst in Example 2 was 35.6 m². 2 / g, pore volume 0.27 cm³ 3 / g.

[0038] Example 3 This embodiment provides a method for preparing a copper-based catalyst, including the following steps: (1) Pre-baking Copper acetate monohydrate and diammonium ethylenediaminetetraacetate were mixed at a mass ratio of 110:4 and ground for 20 min to obtain a copper precursor mixture. The copper precursor mixture was placed in a muffle furnace and heated to 220℃ at a rate of 2.5℃ / min, and held at that temperature for 0.8 h. Then, the temperature was further increased at a rate of 2.5℃ / min to a calcination temperature of 550℃, and held at that temperature for 2 h to obtain a copper oxide matrix.

[0039] (2) Preparation of metal salt composite solution Weigh the following components according to the following mass ratio: 15 parts of metal auxiliary precursor (manganese nitrate and aluminum nitrate mixed in a mass ratio of 10:26), 4.5 parts of tris(hydroxymethyl)aminomethane, 5 parts of citric acid, 3 parts of polyethylene glycol (PEG-400), and 100 parts of solvent (water and ethanol mixed in a mass ratio of 10:12).

[0040] Tris(hydroxymethyl)aminomethane (Tris) was dissolved in a solvent, and citric acid was added and stirred until completely dissolved. Then, a metal precursor was added and stirred until the solid was completely dissolved. The pH of the system was then adjusted to 5.0, and finally polyethylene glycol was added. After mixing evenly, a metal salt composite solution was obtained.

[0041] (3) Impregnation granulation The metal salt composite solution obtained in step (2) was added dropwise to the copper oxide matrix obtained in step (1), controlling the mass ratio of the metal salt composite solution to the copper oxide matrix to be 10:0.75, while shaking. Shaking continued until the content of fine powder smaller than 2 mm in the system was less than 5% of the total mass, and the wet particles with a particle size of 3-6 mm accounted for more than 80% of the total mass, at which point shaking was stopped. Then, the mixture was sealed and allowed to stand at room temperature for 3 hours, allowed to stand under ventilation for 3 hours, and then dried at 80°C for 10 hours to obtain copper-based catalyst precursor particles.

[0042] (4) Staged temperature-controlled roasting The copper-based catalyst precursor particles obtained in step (3) were placed in a muffle furnace and calcined in stages under controlled temperature in an air atmosphere: first, the temperature was increased to 250°C at 3°C / min and kept constant for 1 hour; then the temperature was increased to 550°C at 5°C / min and kept constant for 3 hours to obtain the copper-based catalyst.

[0043] The copper-based catalyst obtained in Example 3 was determined by XRF analysis. The mass percentages of Cu, Al, and Mn were: Cu 75.29%, Al 12.32%, Mn 10.75%; the specific surface area was 34.8 m². 2 / g, pore volume 0.26 cm³ 3 / g.

[0044] Comparative Example To illustrate the technical effects of the present invention, the following comparative examples are provided: Comparative Example 1 (without Tris adjuvant) The preparation steps are the same as in Example 1, except that tris(hydroxymethyl)aminomethane is not added in step (2), and the other conditions are exactly the same as in Example 1.

[0045] The mass percentages of Cu, Al, and Mn in the copper-based catalyst obtained in Comparative Example 1 were determined to be: Cu 75.84%, Al 10.65%, Mn 10.93%; specific surface area 28.5 m². 2 / g, pore volume 0.21cm 3 / g.

[0046] Comparative Example 2 (Urea instead of Tris) The preparation steps are the same as in Example 1, except that in step (2), Tris is replaced with an equimolar amount of urea, and the other conditions are exactly the same as in Example 1.

[0047] The mass percentages of Cu, Al, and Mn in the copper-based catalyst obtained in Comparative Example 2 were determined to be: Cu 75.94%, Al 10.33%, Mn 10.70%; specific surface area 31.2 m². 2 / g, pore volume 0.23cm 3 / g.

[0048] Comparative Example 3 (no citric acid added to the impregnation solution) The preparation steps are the same as in Example 1, except that citric acid is not added in step (2), and the other conditions are exactly the same as in Example 1.

[0049] The mass percentages of Cu, Al, and Mn in the copper-based catalyst obtained in Comparative Example 3 were determined to be: Cu 76.35%, Al 10.83%, Mn 11.61%; the specific surface area was 33.1 m². 2 / g, pore volume 0.25cm 3 / g.

[0050] Comparative Example 4: No EDTA diammonium was added during the pre-calcination stage. The preparation steps are the same as in Example 1, except that diammonium ethylenediaminetetraacetate is not added in step (1). The copper precursor is directly heated to 450°C and calcined for 3 h according to the same heating program to obtain the copper oxide matrix. The other conditions are exactly the same as in Example 1.

[0051] The mass percentages of Cu, Al, and Mn in the copper-based catalyst obtained in Comparative Example 4 were determined to be: Cu 76.75%, Al 10.49%, Mn 11.12%; specific surface area 24.3 m². 2 / g, pore volume 0.19cm 3 / g.

[0052] Catalytic performance evaluation The performance of the catalysts obtained in Examples 1-3 and Comparative Examples 1-4 in the hydrogenation synthesis of 1,4-butanediol from dimethyl succinate was evaluated in a fixed-bed reactor. The evaluation conditions were: reaction temperature 200°C, reaction pressure 6 MPa, hydrogen-to-ester ratio 150, and dimethyl succinate liquid hourly space velocity (LHSV) 0.2 h⁻¹. -1 .

[0053] Calculate the initial dimethyl succinate conversion rate X DMS 1,4-Butanediol selective S BDO and tetrahydrofuran selective S THF X is calculated after 1000 hours of continuous hydrogen addition. DMS S BDO and S THF Dimethyl succinate conversion rate X DMS = (DMS feed rate - DMS residue) / DMS feed rate × 100%, 1,4-Butanediol selectivity S BDO =BDO production rate / (DMS feed rate - DMS residue) × 100%, Tetrahydrofuran selectivity S THF=THF generation amount / (DMS feed amount - DMS remaining amount) × 100%; where DMS feed amount, DMS remaining amount, DMS consumption amount, BDO generation amount and THF generation amount are all amounts of substance; the results are shown in Table 1.

[0054] Table 1

[0055] As shown in the table above, the catalysts obtained in each embodiment of the present invention exhibit excellent catalytic performance in the hydrogenation reaction of dimethyl succinate, with DMS conversion ≥99.98%, BDO selectivity ≥96.13%, and THF selectivity ≤2.11%.

[0056] The BDO selectivity of Comparative Example 1 (without Tris) was only 84.32%, and the THF selectivity was as high as 11.91%, both significantly worse than that of Example 1. This indicates that in the absence of Tris, there is a lack of continuous spatial isolation during the calcination stage, Al and Mn species are prone to migration and aggregation, the pre-dispersion effect of metal components is worse, and ultimately the distribution of active sites becomes unbalanced, side reactions increase, and the BDO selectivity is significantly reduced.

[0057] In Comparative Example 2, after replacing Tris with urea, the BDO selectivity was 87.67% and the THF selectivity was 10.11%, slightly better than Comparative Example 1, but still far lower than Example 1. This indicates that although urea has a certain degree of pore-forming and dispersing effect, urea exists in a neutral molecular form under acidic conditions and does not possess the positive charge characteristics of Tris. Therefore, it cannot be carried to the CuO surface for enrichment through electrostatic attraction, thus affecting the surface Al... 3+ The effect of dispersion retention is limited, so the performance improvement is far less than that of Tris.

[0058] In Comparative Example 3, without the addition of citric acid, the BDO selectivity was 93.28% and the THF selectivity was 3.27%, which was better than Comparative Examples 1 and 2, but lower than that of Example 1. This indicates that citric acid, as the main complexing agent in the impregnation system, plays a role in stabilizing Al in the solution. 3+ Mn 2+ The key role of constructing negatively charged points on the surface; when citric acid is lacking, the carrying effect of Tris cations on the matrix surface through ion-pairing is weakened, the loading uniformity of metal species on the CuO surface decreases, and the catalyst performance is reduced.

[0059] Comparative Example 4 (without EDTA diammonium) showed a BDO selectivity of 89.76% and a THF selectivity of 7.49%, with significantly reduced specific surface area and pore volume. This indicates that EDTA diammonium plays a crucial role as an in-situ pore-forming agent during the pre-calcination stage. The gases released from its decomposition can construct a rich porous structure in the copper oxide matrix, increasing the specific surface area and dispersion of active components in subsequent impregnation. Without the pore-forming effect of EDTA diammonium, the pores in the copper oxide matrix are underdeveloped, making it difficult for Mn and Al active components to disperse uniformly, resulting in decreased catalytic performance.

[0060] After 1000 hours of continuous hydrogenation, the conversion efficiency and BDO selectivity of the catalysts in each example did not decrease significantly, while the performance of the comparative catalysts decreased significantly, especially the selectivity for BDO, with Comparative Example 1 showing the greatest decrease in catalytic performance. This indicates that the catalysts and preparation methods described in the examples can effectively suppress sintering of the catalysts under high temperature and high pressure conditions, significantly extending the continuous operating life of the catalysts in industrial fixed-bed devices.

[0061] Catalyst thermal stability evaluation High-temperature aging treatment: 5.0 g of each of the catalysts obtained in Example 1 and Comparative Example 1 were placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min under air atmosphere, and aged at this temperature for 10 h. After aging, the catalysts were naturally cooled to room temperature to obtain the aged catalyst samples.

[0062] Catalytic performance evaluation before and after aging: The hydrogenation performance of dimethyl succinate was evaluated under the same conditions before and after aging. The evaluation conditions were: reaction temperature 200℃, reaction pressure 6 MPa, hydrogen-to-ester ratio 150, and dimethyl succinate liquid hourly space velocity 0.2 h⁻¹. The reaction products were analyzed by gas chromatography, and the conversion rate X of dimethyl succinate was calculated. DMS and 1,4-butanediol selective S BDO, And the rate of decrease in activity; the calculation results are shown in Table 2; Activity decline rate = (conversion rate before aging - conversion rate after aging) / conversion rate before aging × 100%.

[0063] Table 2

[0064] The thermal stability test results show that after aging at 500℃ for 10 hours, the DMS conversion rate of Example 1 decreased by only 1.02%, and the BDO selectivity remained at 94.89%; while the activity decrease rate of Comparative Example 1 was as high as 10.73%, and the BDO selectivity decreased significantly to 73.84%. This indicates that the present invention, through the combination of composite additives and segmented calcination, maintains a high degree of pre-dispersion of Al and Mn species on the CuO matrix surface, which is conducive to the formation of a stable copper-aluminum spinel phase. The chemical bonding anchoring effect of spinel effectively inhibits the migration and agglomeration of active copper species at high temperatures, endowing the catalyst with excellent thermal stability and anti-sintering properties.

[0065] Unless otherwise stated, the content of each component in this invention is a mass percentage (wt%).

[0066] The above description is merely an exemplary embodiment of the present invention and is not intended to limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the appended claims.

Claims

1. A method for preparing a copper-based catalyst, characterized in that, The steps include: pre-calcination, preparation of metal salt composite solution, impregnation granulation, and calcination; The pre-calcination method is as follows: a copper precursor is mixed with diammonium ethylenediaminetetraacetate and ground for 15-20 min to obtain a copper precursor mixture. The copper precursor mixture is heated to 180-220℃ at a rate of 1.5-2.5℃ / min and held at that temperature for 0.8-1.2 h. The temperature is then further increased to the calcination temperature of 350-550℃ and held at that temperature for 2-4 h to obtain a copper oxide matrix. Tris(hydroxymethyl)aminomethane was dissolved in a solvent, and citric acid was added and stirred until completely dissolved. Then, a metal precursor was added and stirred until the solid was completely dissolved. The pH of the system was then adjusted to 4.5-5.0, and finally polyethylene glycol was added. After mixing evenly, a metal salt composite solution was obtained.

2. The method for preparing a copper-based catalyst as described in claim 1, characterized in that, In the pre-calcination step, the copper precursor is one of copper nitrate, copper sulfate, and copper acetate; The mass ratio of the copper precursor to diammonium ethylenediaminetetraacetate is 100:3-4.

3. The method for preparing a copper-based catalyst as described in claim 1, characterized in that, In the step of preparing the metal salt composite solution, the metal auxiliary precursor is a mixture of manganese nitrate and aluminum nitrate in a mass ratio of 10:24-26. The solvent is a mixture of water and ethanol in a mass ratio of 10:8-12; The mass ratio of the metal additive precursor, tris(hydroxymethyl)aminomethane, citric acid, polyethylene glycol, and solvent is 10-15:3.5-4.5:4-5:2-3:

100.

4. The method for preparing a copper-based catalyst as described in claim 1, characterized in that, The impregnation granulation method involves dripping a metal salt composite solution onto a copper oxide matrix and continuously shaking it until the content of fine powder smaller than 2 mm in the system is less than 5% of the total mass, and the wet particles with a particle size of 3-6 mm account for more than 80% of the total mass. Then, the shaking is stopped. Subsequently, the mixture is sealed and left to stand at room temperature for 2-3 hours, then left to stand under ventilation for 2-3 hours, and then dried at 50-80℃ for 10-14 hours to obtain copper-based catalyst precursor particles.

5. The method for preparing a copper-based catalyst as described in claim 4, characterized in that, In the impregnation granulation step, the mass ratio of the metal salt composite solution to the copper oxide matrix is ​​10:0.65-0.

75.

6. The method for preparing a copper-based catalyst as described in claim 4, characterized in that, The calcination method involves calcining copper-based catalyst precursor particles in an air atmosphere at controlled temperatures in stages to obtain a copper-based catalyst.

7. The method for preparing a copper-based catalyst as described in claim 6, characterized in that, The staged temperature-controlled calcination is as follows: first, the temperature is increased to 230-250℃ at 1-3℃ / min and held at this temperature for 1-2 hours; then, the temperature is increased to 450-550℃ at 2-5℃ / min and held at this temperature for 3-5 hours to obtain the copper-based catalyst.

8. A copper-based catalyst prepared by any one of claims 1-7.

9. The use of the copper-based catalyst prepared by any one of claims 1-7 in the hydrogenation of dimethyl succinate to 1,4-butanediol.

Citation Information

Patent Citations

  • High selectivity hydrogenation catalyst for preparing 1,4-butanediol by hydrogenation of dimethyl succinate as well as preparation method and application of high selectivity hydrogenation catalyst

    CN102784651B

  • A method for preparing a highly efficient copper-manganese-aluminum catalyst for the production of 1,4-butanediol.

    CN103566945B

  • Preparation method of hydrogenation catalyst

    CN103769157B

  • Copper-chromium catalyst and its preparation method and use

    CN105709760A

  • Ester hydrogenation catalyst, preparation method and application of ester hydrogenation catalyst in preparation of 1, 4-butanediol through dimethyl succinate hydrogenation

    CN117258798A